The Efficacy of Sauropus androgynus Leaves Extract To Improve Cognitive Function in Wistar Rats Induced Alzheimer’s - Rachmat Hidayat; Raden Ayu Adelia Safitri; Tungki Pratama Umar; Arindi Maretzka (HM Publisher, 2018)
Background Sauropus androgynus leaves is the substance which has the potency to prevent degenerative processes. Sauropus androgynus leaves has flavonoid as the main component. Flavonoid has antioxidant and anti neuro-inflammation that can be used to prevent Alzheimer dementia. Research purpose is knowing the effect of Sauropus androgynus leaves for the cognitive function and β-amyloid expression in the hippocampus of wistar rats. Methods Reseacrh was done by in vivo method, where male wistar rats (n=24) were distributed to six groups which consisting of four rats. Group 1: Normal control, group 2: positive control, group 3: standard treatment (B12 vitamin), group 4, 5 and 6 were give Sauropus androgynus leaves extract with the dose of 75 mg/kgBB, 150 mg/kgBB and 300 mg/kgBB, respectively for 28 days. Cognitive function was evaluated by t-maze test, where hippocampal β-amyloid expression was tested by immunohistochemistry. Results Time differences (day 0-28), alternation ratio distinction (day 0-28) and β-amiloid expression were: group 1 (1,84 second; 0,23 unit; 0,518%), group 2 (56,78 second; -0,42 unit; 40,036%), group 3 (34,46 second; -0,25 unit; 33,08%), group 4 (32,83 second; -0,09 unit; 28,88%), group 5 (-3,91 second; 0,42 unit; 14,728%), group 6 (24,25 second; 0,42 unit; 9,4%). Conclusion Sauropus androgynus leaves extract at the dose of 150 mg/kgBB and 300 mg/kgBB can maintain cognitive function by decreasing hippocampal β-amyloid formation.